Beliefs, knowledge, and oral health practices of the Mapuche-Williche population of Isla Huapi, Chile - Manríquez-Urbina, José; Misrachi-Launert, Clara; Fajreldin-Chuaqui, Valentina; Kuwahara-Aballay, Kiyoshi; Verdaguer-Muñoz, Carolina (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: In Chile, the law recognizes the existence of eight indigenous peoples, representing 4.6% of the total population; 87.3% of them are Mapuche. This population presents worse economic, educational and health indicators than the general population. Isla Huapi is a rural locality in the South of the country. It is geographically and culturally isolated; it lacks health care access and suffers poverty and social marginalization. The objective of this study was to describe the determinants of oral health behavior in the Mapuche-williche population from Isla Huapi and their distribution by sex and age. Methods: this was a descriptive cross-sectional study using instruments of beliefs, knowledge and oral health practices previously validated in the population of Isla Huapi, consisting of 417 subjects, 98% of whom are Mapuche. The analysis was performed with STATA® 11. Results: 77 subjects (53% females) were interviewed. 66% of them mentioned that “bad washing” is related to dental caries, 62% “uses natural remedies” for oral health care, and 80% admitted brushing their teeth at least twice a day. There was significant difference in terms of “motivation” to consult the dentist (higher motivation levels in women) and “perceived barriers to health care access” (older adults perceive more difficulties). Conclusions: there is plenty of information on the impact of social and behavioral determinants (SBD) in the implementation of health promotion strategies. However, in Chile there are few specific oral health programs for indigenous peoples. This is a pioneering study in establishing a cross-cultural work in oral health.